2021
DOI: 10.2217/fon-2020-1160
|View full text |Cite
|
Sign up to set email alerts
|

Upregulated Expression of MTFR2 as a Novel Biomarker Predicts Poor Prognosis in Hepatocellular Carcinoma by Bioinformatics Analysis

Abstract: Aim: The authors investigated the clinical role of MTFR2 in hepatocellular carcinoma (HCC) progression. Results: MTFR2 expression and methylation were abnormal in HCC tissues, and HCC patients with increased MTFR2 expression or methylation had poor or better overall survival, respectively. In addition, increased MTFR2 expression was correlated with age, grade, cancer stage and T stage. MTFR2 was an independent predictor of dismal prognosis in HCC patients. MTFR2 was involved in HCC progression by modulating th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…However, the mechanism of m6A/m1A/m5C regulated genes in HCC progression remains to be confirmed in future studies. Currently, targeted therapy and immunotherapy are among the treatment options available to HCC patients (2,(35)(36)(37)(38). For example, PD-1 inhibitors are well tolerated by HCC patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the mechanism of m6A/m1A/m5C regulated genes in HCC progression remains to be confirmed in future studies. Currently, targeted therapy and immunotherapy are among the treatment options available to HCC patients (2,(35)(36)(37)(38). For example, PD-1 inhibitors are well tolerated by HCC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Liver cancer is one of the most prevalent cancers worldwide. Hepatocellular carcinoma (HCC) accounts for approximately 80% of liver cancer (1,2). Recent studies have demonstrated that targeted therapy and immunotherapy significantly affect HCC patient survival (3)(4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…KIF20A downregulation may decrease the proliferation and induce the G1 arrest of HCC cells [ 32 ]. CDCA8 is in relation to unfavorable stage and survival outcomes of HCC [ 33 ]. CDCA8 inhibition weakens HCC growth and stemness through restoring ATF3 and inactivating AKT/ β -catenin axis [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, exploring the underlying mechanism of the development of HCC is important for identifying early diagnostic biomarkers for HCC and for improving the prognosis of HCC. Although various studies have attempted to discover new biomarkers for predicting the prognosis of HCC or detecting early HCC, 16,17 these biomarkers lack effectiveness for HCC, and most studies have focused on whole-stage HCC.…”
Section: Discussionmentioning
confidence: 99%